READING ALOUD ANECDOTES: INVESTIGATING THE PHONOLOGICAL FEATURES OF SEVENTH-GRADE EFL STUDENTS - Nurmaliana Sari Siregar; Fitri Ani (UIN Sumatera Utara, 2026)
This study focuses on phonology is uttered by the students grade 7. Phonology refers to study how sounds are organized and used in natural languages. It also expands about the abstract system and patterns of those sounds within a specific language. It looks at the